The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-90501-2
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in telomerase reverse transcriptase (TERT) modifies cancer risk in Lynch syndrome patients harbouring pathogenic MSH2 variants

Abstract: Individuals with Lynch syndrome (LS), have an increased risk of developing cancer. Common genetic variants of telomerase reverse transcriptase (TERT) have been associated with a wide range of cancers, including colorectal cancer (CRC) in LS. We combined genotype data from 1881 LS patients, carrying pathogenic variants in MLH1, MSH2 or MSH6, for rs2075786 (G>A, intronic variant), 1207 LS patients for rs2736108 (C>T, upstream variant) and 1201 LS patients for rs7705526 (C>A, intronic variant). The risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…In particular, two studies confirmed the association of genomic regions 8q23.3 and 11q23.1 with CRC risk in individuals with LS ( 48 , 51 ). A recent study found an association between rs2075786, a SNP of the gene encoding telomerase reverse transcriptase ( TERT ) and cancer risk in individuals with germline MSH2 mutation in a large international cohort ( 50 ). Nevertheless, studies leveraging these results to construct polygenic risk scores in this cohort are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two studies confirmed the association of genomic regions 8q23.3 and 11q23.1 with CRC risk in individuals with LS ( 48 , 51 ). A recent study found an association between rs2075786, a SNP of the gene encoding telomerase reverse transcriptase ( TERT ) and cancer risk in individuals with germline MSH2 mutation in a large international cohort ( 50 ). Nevertheless, studies leveraging these results to construct polygenic risk scores in this cohort are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Similar numbers were screened who carried pathogenic variants in MLH1, which attests to the veracity of this study. Two SNPs, rs2075786 and rs2736108 appeared to have an effect on the age of colorectal cancer diagnosis whereas there was no effect observed in MLH1 or MSH6 PV carriers [ 23 ]. It was observed that heterozygote carriers of the rs2736108 SNP were at greater risk of cancer compared to their wildtype counterparts.…”
Section: Problems Associated With Identifying Modifier Genes In Lynch...mentioning
confidence: 99%
“…The number of homozygous carriers of the rs2736108 SNP were minimal (46 in total) with only 27 cancer carriers and 19 cancer free carriers, which negated any meaningful interpretation. Carriers of the minor allele of rs2075786 were more likely to develop cancer at an earlier age compared to heterozygous or wildtype allele carriers [ 23 ].…”
Section: Problems Associated With Identifying Modifier Genes In Lynch...mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA mismatch repair (MMR) genes, are key factors in response to basebase mismatches and small insertion/deletions caused by misincorporation errors during DNA replication (15). Studies indicated that SNPs of specific MMR genes can affect the expression of genes, activity of enzymes and individual repair efficiency to DNA damages (16)(17)(18). As one of the most important MMR genes, MSH2 plays a critical role in repairing mismatched DNA base.…”
Section: Introductionmentioning
confidence: 99%